TRADE SECRET PROTECTION IN INDIA - Chinmaya Kumar Mohapatra, Amrita Mishra (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The need for the globalized economy today is trade secret. Often developers / innovators do not wish to license the product / process cost of the predominant need for full disclosure. The security of trade secrets in India has usually not been a topic of much debate in the past. Trade secrecy is a simple way to address these problems. The writer wants to clarify the regulatory structure of this IP domain Security in India in this research article. This study would include overview of the legislation on clandestine / secret trade as it exists today. Trade secrets security is important for promoting creative initiatives, global investment and promoting fair competition. Trade secrets offer a feisty advantage over the competition and therefore one must ensure that he successfully defends his subtle business knowledge from his competitors. Trade concealment a modern form of IP is very vital whereas is gaining sufficient popularity for the reason that in age of growing globalization, the loss or success of each company rest on on its secrets, initiating them to remain secrets of government or consumer knowledge. Through such a paper the author is making an effort to highlight the laws that deal with trade secrets in India.